Wergild or blood money from the Islamic point of view - Zarifi, Abdul Qodus; Burhani, Obaidullah (Technium Business and Management, 2022)
The information of this research is summarized as follows. Wergild: in terms of lexical is " Farewell " to financial that The killer pays for the victim in exchange for her life, and it's Vedat origin is to the conquest of Waw and the stillness of the Dal, is called infinitive to Dit, and then Fa has been removed in exchange for Ha.atonement : called wergild for what is obligatory without spirit and instead of spirit and government of justice also applies. Also, wergild existed before Islam, the purpose of wergild and blood money is to prevention and forbidding the perpetration of crime and support of the people's life Therefore wergild and blood money should be so hard and the amount should be huge and serious. The Prophet (peace and blessings of Allah be upon him) himself stated that a Muslim man is a free camel, wergild should be paid from the property of convict whether is a man or is a woman and wergild is obligatory on him. That is to say, the murder's wergild is when nemesis should be abolished. The blood money of a woman is half the blood money of a man, and also the blood money of her parts of body and the blood money of her wounds is half the blood money of a man's parts of body and injuries, and most scholars agree on this. The information of this research is summarized as follows. Wergild: in terms of lexical is " Farewell " to financial that The killer pays for the victim in exchange for her life, and it's Vedat origin is to the conquest of Waw and the stillness of the Dal, is called infinitive to Dit, and then Fa has been removed in exchange for Ha.atonement : called wergild for what is obligatory without spirit and instead of spirit and government of justice also applies. Also, wergild existed before Islam, the purpose of wergild and blood money is to prevention and forbidding the perpetration of crime and support of the people's life Therefore wergild and blood money should be so hard and the amount should be huge and serious. The Prophet (peace and blessings of Allah be upon him) himself stated that a Muslim man is a free camel, wergild should be paid from the property of convict whether is a man or is a woman and wergild is obligatory on him. That is to say, the murder's wergild is when nemesis should be abolished. The blood money of a woman is half the blood money of a man, and also the blood money of her parts of body and the blood money of her wounds is half the blood money of a man's parts of body and injuries, and most scholars agree on this.